2023
DOI: 10.7554/elife.76300
|View full text |Cite
|
Sign up to set email alerts
|

A systematic assessment of preclinical multilaboratory studies and a comparison to single laboratory studies

Abstract: Background: Multicentric approaches are widely used in clinical trials to assess generalizability of findings, however they are novel in laboratory-based experimentation. It is unclear how multilaboratory studies may differ in conduct and results from single lab studies. Here we synthesized characteristics of these studies and quantitatively compared their outcomes to those generated by single laboratory studies.Methods: MEDLINE and Embase were systematically searched. Screening and data extractions were compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…It is highly likely that effect sizes reported throughout the social-psychology literature are frequently inflated because of publication bias and p -hacking. The shrinking of effect sizes has also been noted in medical research (Hunniford et al, in press), where it was attributed to superior methodological rigor, including larger samples, in multisite replications than in single-site original studies. Fiedler and Prager (2018) proposed that regression toward the mean (i.e., the statistical tendency for extreme observations or results to be followed by others closer to the mean) almost guarantees that replications (whether multilab or single lab) will produce smaller effects than original studies.…”
Section: Resultsmentioning
confidence: 85%
“…It is highly likely that effect sizes reported throughout the social-psychology literature are frequently inflated because of publication bias and p -hacking. The shrinking of effect sizes has also been noted in medical research (Hunniford et al, in press), where it was attributed to superior methodological rigor, including larger samples, in multisite replications than in single-site original studies. Fiedler and Prager (2018) proposed that regression toward the mean (i.e., the statistical tendency for extreme observations or results to be followed by others closer to the mean) almost guarantees that replications (whether multilab or single lab) will produce smaller effects than original studies.…”
Section: Resultsmentioning
confidence: 85%
“… 40 , 41 In a systematic review from 2023, 16 multicenter animal studies across all research disciplines were identified. 42 Twelve of 16 studies were published in 2015–2020 illustrating an increased focus in the recent years. Interestingly, the review identified that study quality was higher for multilaboratory studies versus single laboratory studies, although none of the identified multilaboratory had low risk of bias.…”
Section: The Future Of Animal Studiesmentioning
confidence: 99%
“…This will reduce heterogeneity but at the cost of external validity. 42 This is also illustrated in the cardiac arrest multilaboratory study where experimental procedures such as anesthesia and chest compression techniques differed between laboratories. Furthermore, multilaboratory studies are costly and whether they improve identification of treatments that results in successful clinical translation is unknown.…”
Section: The Future Of Animal Studiesmentioning
confidence: 99%
“…Multi-centre studies can provide a more diverse patient population, reducing selection bias, and enhancing the external validity of the findings. 7 We are interested in understanding the feasibility and potential challenges of expanding this research to include multiple centres.…”
mentioning
confidence: 99%